Posterior Fusion for the Subaxial Cervical Spine: A Review of the Major Techniques. Issue 2 (July 2020) - Mikhail, Christopher M.; Dowdell, James E.; Hecht, Andrew C.
Posterior fusion is a powerful tool to address pathology of the cervical spine, but the decision to fuse at any level should be made with great care. Various methods and constructs for posterior cervical fusion exist, all of which aim to restore the posterior tension band's ability to resist flexion forces. We identified articles regarding posterior fusion of the subaxial cervical spine in MEDLINE, Google Scholar, and PubMed. This article is a narrative review of earlier and current concepts regarding the posterior fusion of the subaxial cervical spine, including wiring, translaminar screws, lateral mass screws, and pedicle screws, weighing the strengths and weakness of the different modalities that the surgeon should bear in mind in creating operative plans individualized to patient pathology.